QUANTITATIVE RISK ASSESSMENT OF HYDROGEN PRODUCTION FACILITY - SHARIMAN, AFIQAH SYAHIRAH (2023)
The increasing demand for hydrogen as a clean and versatile energy carrier has led to the rapid growth of hydrogen production facilities.